(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This paper explores niche intersections among psycholinguistics, inclusive educational material design, and language education, with the aim of advancing equitable, cognitively-informed pedagogical practices. While each domain has developed independently, their convergence offers fertile ground for innovative research and application. Psycholinguistics provides insights into the cognitive processes underlying language acquisition, comprehension, and production, which can inform the development of more accessible and effective instructional materials. Simultaneously, inclusive material design grounded in Universal Design for Learning (UDL) and culturally responsive pedagogy aims to accommodate diverse learners, including those with disabilities, linguistic minority backgrounds, and neurodivergent profiles. This paper investigates how principles from psycholinguistics can be operationalized in the creation of inclusive language learning materials. Specific attention is given to the processing of syntactic complexity, lexical frequency, and semantic transparency in learners with varied cognitive and linguistic profiles. Furthermore, the paper examines how inclusive materials may reduce cognitive load, enhance working memory utilization, and support deeper semantic encoding in multilingual and neurodiverse classrooms. This study highlights under-researched areas such as the acquisition of inclusive pronouns in second-language learners, the psycholinguistic processing of gender-neutral structures, and the design of language input for learners using augmentative and alternative communication (AAC) systems. Methodological approaches draw from experimental psycholinguistics, discourse analysis, and design-based research in education. By integrating these fields, this paper argues for a model of language education that is both empirically grounded and socially inclusive. The proposed framework has implications for curriculum development, teacher training, and policy-making in multilingual and multicultural educational contexts. Ultimately, the paper advocates for a shift toward pedagogical practices that are not only linguistically effective but also cognitively and ethically responsive to learner diversity.